Tetrodotoxin block of A-fibre afferents from skin and muscle: a tool to study pure C-fibre effects in the spinal cord - Steffens, Heinz; Eek, Björn; Trudrung, Peter; Mense, Siegfried (Pflügers Archiv, 2003)
The properties of tetrodotoxin (TTX)-resistant C-fibre afferents of the dorsal roots were tested in Sprague-Dawley rats. Dorsal roots (L4-L6) were blocked with TTX (0.5-1 µM) and the amplitude of the first response of the dorsal horn superficial interneurones (cord dorsum potential, CDP) to electrical stimulation of peripheral C-fibres in combination with natural noxious stimulation was taken as measure for intact conductivity of different kinds of noxious input by means of the C-fibre refractory period. After blockade of dorsal roots with TTX, formerly masked CDPs from muscle C-fibre afferents were uncovered. Noxious pressure to the gastrocnemius soleus muscle belly and noxious pinch to the calcanean tendon proved to be TTX resistant and therefore was propagated centrally. For cutaneous heat nociceptors it could also be shown that conductivity was intact after blockade of the dorsal roots with TTX. However, we could not exclude the TTX resistance of non-nociceptive receptors of muscle or skin. Nevertheless, blockade of afferents with TTX together with suitable stimulation techniques proves to be a reliable method to investigate central effects from C-fibre afferents without contaminating effects from A-fibres in the rat.